Mastering the art of oral presentations : winning orals, speeches, and stand-up presentations - Stewart, John Parker; Fulop, Don, 1950- (Wiley, 2019)
"Formal oral presentations communicate a message in a way that is unlike any other method of delivery. Nothing is more influential than a dynamic, face-to-face presentation followed by a lively discussion among the various stakeholders. A powerful presentation will endure in the minds of the audience and ultimately become a motivating force that positively influences their decision making. To make your presentation memorable, you must understand what makes people receptive to what you have to say, deliver a credible and convincing message, and stay focused on your topic. This involves a great deal of deliberate, thorough preparation. It must not be treated as an impromptu event. To ensure the success of your targeted outcome, your presentation must be thoughtfully planned, it must be insightful, and it must be compelling"--